Determinants of cryptocurrency adoption behavior in Malaysia - Wong, Siew Chin; Teoh, Melissa Teng Tenk; Yap, Angeline Kiew Heong; Zakiah Saleh (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cryptocurrency has proven to be an enabling force for financial service transformation. It allows users to perform transactions via blockchain technology that bypasses the involvement of conventional financial intermediaries. In local context, the acceptance of cryptocurrency is rather low as compared with other developed countries. The requirement of large consumer market base is the main challenges for cryptocurrency’s adoption. Thus, the aim of this study is to determine the relationship between output quality, perceived accessibility, result demonstrability and perceived security and adoption behavior of cryptocurrency as an additional mode of internet/online transaction methods. The data was collected from a sample of 553 respondents from different age groups ranging from under 21 to over 60 years old. The PLS-SEM results demonstrated that there are significant positive relationships between output quality, result demonstrability and perceived security and the users’ adoption behavior to use cryptocurrency. The paper provides an insight for explaining the adoption behavior of cryptocurrency. The findings are insightful to develop effective financial management mechanisms and interventions, which is important to enhance the confidence and understanding level toward the adoption of cryptocurrencies among existing and potential users.